Model Personal Branding Management Trainee as a Means of Improving Corporate Brand (Case Study on Retail Company PT Home Center Indonesia) - M. Darul Muttaqin; Jamalulail Jamalulail (Budapest International Research and Critics University, 2022)
Branding is a common thing in the world of marketing, whether it is done by groups such as organizations, institutions or companies or individuals. In the world of marketing, branding is done to distinguish one product from another so that it brings out its distinctive characteristics. Along with the development of the branding context, now branding has penetrated into many lines, including one's self-development. This is what is known as personal branding. This study reviews the personal branding analysis of Management Trainees at the PT Home Center Indonesia company. Management Trainee is a position acceleration program created by the company in order to create a cadre of young leaders to occupy high enough positions in the company in a short period of time to get the position of Deputy Operational Manager or even Area Manager. One of the objectives of this research is to explore the Personal Branding model created by Management Trainees in improving the Corporate Brand of PT Home Center Indonesia. This is the main focus of this research because self-existence is a fundamental thing that must exist in a person, including Management Trainees at PT Home Center Indonesia. This study uses a qualitative descriptive method that is supported by eight personal branding concepts by Peter Montoya.